Optimasi proses pemindaian 3D untuk meningkatkan representasi digital produk keramik - Pande Putu Ranjip Astika; I Gusti Bagus Budi Dharma (Institut Seni Indonesia Yogyakarta, 2026)
The digitalization of ceramic craft products is essential to improve the competitiveness and market reach of small-scale enterprises. However, two-dimensional visualization often fails to accurately represent the shape, color, and texture of these products. This study aims to optimize the three-dimensional (3D) scanning process using the EINSTAR Shining 3D Scanner to produce precise digital models. Experiments were conducted on ceramic mugs with three resolution levels (high, medium, low) and two scanning positions (normal and inverted) to obtain complete models. The results indicate that high-resolution scanning (0.2 mm) provides the best geometric and texture detail, while dual-position scanning effectively resolves coverage limitations. Comparisons between digital models and physical objects demonstrate high accuracy in terms of geometry and color, although micro-textures are only partially captured. These findings offer practical technical guidance for small-scale ceramic producers in selecting efficient scanning configurations, enabling improved digital product representation while maintaining manageable resource and processing demands,